An object-oriented, individual-based approach for simulating the dynamics of genes in subdivided populations - Kool, Johnathan T. (Ecological informatics, 2009)
An object-oriented, individual-based simulation framework was developed for modeling the diffusion of genetic material in subdivided populations. Objects representing individual organisms were defined, each with a unique genotype composed of gene objects. The organisms mate and reproduce, and progeny disperse or recruit back to their native population through the use of a Movement interface. The object-oriented approach is also linked to analytical theory through the development of matrix-based equations. An implementation of the model demonstrates how changes to basic population parameters affect spatial and temporal genetic structure. Scalar changes to the system affect the duration over which processes occur as well as the degree of variance, but appear to leave overall structural patterns unchanged. Object-oriented programming provides some unique advantages for modeling population genetic processes, including the use of abstraction and implementation, as well as the ability to accommodate complex, heterogeneous behavior.